Novel process and catalytic materials for converting CO2 and H2 containing mixtures to liquid fuels and chemicals. (7th October 2015) - Meiri, Nora; Dinburg, Yakov; Amoyal, Meital; Koukouliev, Viatcheslav; Nehemya, Roxana Vidruk; Landau, Miron V.; Herskowitz, Moti
Abstract : Carbon dioxide and water are renewable and the most abundant feedstocks for the production of chemicals and fungible fuels. However, the current technologies for production of hydrogen from water are not competitive. Therefore, reacting carbon dioxide with hydrogen is not economically viable in the near future. Other alternatives include natural gas, biogas or biomass for the production of carbon dioxide, hydrogen and carbon monoxide mixtures that react to yield chemicals and fungible fuels. The latter process requires a high performance catalyst that enhances the reverse water-gas-shift (RWGS) reaction and Fischer–Tropsch synthesis (FTS) to higher hydrocarbons combined with an optimal reactor system. Important aspects of a novel catalyst, based on a Fe spinel and three-reactor system developed for this purpose published in our recent paper and patent, were investigated in this study. Potassium was found to be a key promoter that improves the reaction rates of the RWGS and FTS and increases the selectivity of higher hydrocarbons while producing mostly olefins. It changed the texture of the catalyst, stabilized the Fe–Al–O spinel, thus preventing decomposition into Fe3 O4 and Al2 O3 . Potassium also increased the content of Fe5 C2 while shifting Fe in the oxide and carbide phases to a more reduced state. In addition, it increased the relative exposure of carbide iron on the catalysts surface, the CO2 adsorption and the adsorption strength. A detailed kinetic model of the RWGS, FTS and methanation reactions was developed for the Fe spinel catalyst based on extensive experimental data measured over a range of operating conditions. Significant oligomerization activity of the catalyst was found. Testing the pelletized catalyst with CO2, CO and H2 mixtures over a range of operating conditions demonstrated its high productivity to higher hydrocarbons. The composition of the liquid (C5+ ) was found to be a function of the potassium content and the composition of the feedstock.